Empirical Study on the Influence of Internet Use on the Employability of Local College Students - He, Peiyi (International Journal of Social Sciences and Public Administration, 2024)
Based on the data of China Family Panel Studies (CFPS) in 2020, this paper analyzes the impact of Internet use on the employability of local college students through OLS and logit regression models. The study found that the Internet has become an important tool for local college students to improve their employability. Students who actively participate in online learning, use career recruitment platforms and social media to expand career networks in local colleges and universities show stronger competitiveness in terms of professional skills, comprehensive quality and job search skills. The importance of Internet use to work, learning and information channels has a significant impact on the employability of local college students, and has a significant moderating effect. Through heterogeneity analysis, it is found that the impact of Internet use on the employability of local college students in eastern China is significantly higher than that in central and western China : the employability of college students with urban household registration is higher than that of local college students with rural household registration, and the employability of female local college students is lower than that of male local college students. Therefore, this study suggests that local colleges and universities should further guide students to make rational use of Internet resources and strengthen network literacy education, so as to better adapt to the employment market demand and promote high-quality employment of graduates.